System Usability Scale (SUS) Pada Bank Sampah Digital Sebagai Solusi Penanganan Sampah - Desyanti Desyanti; Mustazihim Suhaidi; Febrina Sari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
As time goes by and the number of human needs causes organic and inorganic waste to accumulate, the Environment and Hygiene Service provides garbage disposal sites at several points, but still the garbage is scattered on the roadside, and the smell disturbs road users who pass. Garbage accumulation is more focused on inorganic waste which is managed by the waste bank unit. The Department of Environment and Hygiene has several units of garbage bins scattered in several sub-districts in the city of Dumai, one of which is the Bukit Kapur Garbage Bank Unit, currently the management of the waste bank is still using written media to record transaction data on waste sales, reporting is sometimes too late, The accumulation of sales funds often results in miscalculations. For this reason, create a digital application that can help the Waste Bank unit in managing inorganic waste. With this digital waste bank application, it can make it easier for officers to manage waste management and can provide information related to waste banks to the surrounding community. Testing this application using the System Usability Scale (SUS) to evaluate the usability of the application that has been designed. The usability value of this Digital Waste Bank application is 77.8 which means it is in the acceptable category.